Experimental analysis of forced convective heat transfer of nitrate salt in a spirally grooved tube at high Reynolds numbers and temperatures. (1st May 2023) - Frantz, Cathy; Buck, Reiner; Röger, Marc; Hoffschmidt, Bernhard
Highlights: Review of the literature of the forced convective heat transfer of molten salts in enhanced tubes. Measurement of the forced convective heat transfer of Solar Salt in a spirally grooved tube for 11000 < R e < 285000. Comparison of the measured friction factor in a spirally grooved and a smooth tube to correlations from the literature. Measurement of the Nusselt number at film temperatures above the chemical stability temperature limit of Solar Salt. Abstract: The forced convective heat transfer and pressure difference of molten nitrate salt in a spirally grooved tube with a relative groove height e/2ri =0.017, a relative groove pitch p/2ri =0.913 and groove angle α=73.8° is experimentally investigated using a water-cooled induction heater setup. The data is provided for Reynolds numbers ranging between 11000 up to 285000 and Prandtl numbers from 3.7 to 10. The experiments are carried out for bulk salt temperatures ranging between 300 and 550 °C and for heating flux densities between 330 and 930 kW/m². Inner wall temperatures up to 633 °C are achieved with the setup, thus providing data on the behavior of the forced convective heat transfer as a function of inner wall temperature. The data is compared to the measurement results obtained with the same setup and a circular smooth tube as well as correlations and data from the literature in order to deduce relative Nusselt numbers and friction factors.